Nancy Fraser and Participatory Parity:Reframing Social Justice in South African Higher Education - Hodgkinson-Williams, Cheryl (Critical Studies in Teaching and Learning, 2023)
Bozalek, V. & Hölscher, D. & Zembylas, M. (eds.) 2020. Nancy Fraser and Participatory Parity: Reframing Social Justice in South African Higher Education. London: Routledge.